Impact of Product Quality, E-Service Quality, and Rewards on Customer Retention with Commitment Mediation. - Ahmad Surya Fadilah; Yuniarti Fihartini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the factors influencing customer retention at Surya Fresh MSMEs in Depok City, West Java. The primary issue identified is the instability of customer retention, which is mainly attributed to intense market competition, the rapid pace of digital marketing, and the evolving customer expectations in the modern business environment. This study aims to analyze the impact of product quality, e-service quality, and reward programs on customer retention, with relationship commitment as a mediating variable. A quantitative approach with an explanatory research design was employed to test the relationships among variables. Primary data were collected through a Likert-scale questionnaire from 224 Surya Fresh customers using a simple random sampling technique. Data analysis was conducted using the PLS-SEM method in SmartPLS, including validity, reliability, and structural model assessments. The findings indicate that product quality, e-service quality, and reward programs significantly influence relationship commitment and customer retention. Moreover, relationship commitment was found to mediate the effects of these three factors on customer retention, highlighting its importance in enhancing customer loyalty. High e-service quality, superior product quality, and attractive reward programs foster strong emotional connections with customers, which are crucial for sustaining long-term customer loyalty. The study concludes that product quality, e-service quality, and reward programs have a positive and significant impact on relationship commitment and customer retention at Surya Fresh. Relationship commitment is confirmed as a key mediator. To further improve retention, Surya Fresh should focus on enhancing product availability, administrative responsiveness, and offering diverse promotional programs. Future studies may apply this model in different industries and integrate qualitative methods for deeper insights.